(untitled) (American Journal of Islam and Society, 1989)
I. The Concept of the Discipline of Education A. Fields of knowledge are diversified, and touch upon almost every aspect of life and the universe, including the physical, societal, spiritual and material aspects. Various theories of knowledge are proposed by man to deal with its classification, acquisition and use in life situations. The discipline of education deals with the question of teaching and learning of various disciplines of knowledge by teachers and students with the hope of changing the behavior of the learner to adapt to society and develop the capabilities necessary to become an effective human being. Education, then, is an applied discipline of knowledge which is a composite of other social and humanistic disciplines. It concerns itself with changing the behavior of the learner, in terms of information, skills and attitudes. Education guides human beings in a certain direction delineated by the values of the society or a certain ideology using know-how, methods, and technologies of teaching compatible with their nature and style of learning. Education, then, is both a process and a result of a process. The results or objectives of education reflect the dimensional value system of the society, and thus education is never a neutral discipline. Education cannot be neutral since it produces an individual with a personality that represents the value system of the society and its ideology in life. The content of the educational discipline depends on its interaction with other social and humanistic disciplines which are also partly value oriented and partly experimentally oriented. The process of education or the know-how, including use of methods, ...